High Entropy Enabling the Reversible Redox Reaction of V4+/V5+ Couple in NASICON‐Type Sodium Ion Cathode. Issue 12 (2nd February 2023) - Li, Meng; Sun, Chen; Ni, Qing; Sun, Zheng; Liu, Yang; Li, Yang; Li, Lei; Jin, Haibo; Zhao, Yongjie
Abstract: NASICON‐type Na3 VM(PO4 )3 (M: transition metals) cathodes usually suffer from poor cycling stability in the voltage region of above 4 V versus Na + /Na owing to irreversible phase transition and severe structural distortion. Herein, the high entropy concept is extended to NASICONs and Na3 VAl0.2 Cr0.2 Fe0.2 In0.2 Ga0.2 (PO4 )3 (NVMP) with high purity is obtained. The NVMP achieves a highly reversible specific capacity of 102 mAh g −1 (2.5–4.4 V vs Na + /Na) via the successive redox reaction of V 3+ /V 4+ /V 5+ together with a long‐term lifespan of 5000 cycles at 20 C (a capacity retention of 86.8%). Even at an extreme temperature of −20 °C, the NVMP cathode can still provide excellent cycling performance (a capacity retention of 94.2% at 5 C after 1000 cycles). Moreover, the increased configurational entropy in the electrode renders a quite small cell volume change of 1.1%. The sodium ion storage mechanism containing solid solution‐type in the voltage range of 2.5–3.8 V and bi‐phasic in 3.8–4.4 V is revealed by ex situ XRD analysis. Pairing with a hard carbon anode, NVMP//HC cell offers a specific capacity of 81 mAh g −1 at 0.2 C based on the cathode mass. This high‐entropy engineering is expected to be widely applicable for the development of polyanionic electrode materials. Abstract : A high‐entropy NASICON‐type Na3 VAl0.2 Cr0.2 Fe0.2 In0.2 Ga0.2 (PO4 )3 (NVMP) cathode is proposed. The irreversible phase transition induced by the redox reaction of the V 4+ /V 5+ couple (4.0 V versus Na + /Na) in a NASICON matrix is apparently depressed by the high entropy effect. The NVMP cathode offers a reversible specific capacity of 102 mAh g ‐1 and excellent electrochemical performance at 25 and −20 °C.